Monetary Materialities of Peer-Produced Knowledge: The Case of Wikipedia and Its Tensions with Paid Labour - Arwid Lund; Juhana Venäläinen (tripleC: Communication, Capitalism & Critique)
This article contributes to the debate on the possibilities and limits of expanding the sphere of peer production within and beyond capitalism. As a case in point, it discusses the explicit and tacit monetary dependencies of Wikipedia, which are not only due to the need to sustain the technological structures that render the collaboration possible, but also about the sustenance of the peer producers themselves. In Wikipedia, the “bright line” principle for avoiding a conflict of interest has been that no one should be paid for directly editing an article. By examining the case of Wiki-PR, a consultant firm allegedly involved in helping more than 12,000 clients to edit Wikipedia articles until 2014, the goal of the analysis is to shed light on the paradoxical situation where the institution for supporting the peer production (Wikimedia Foundation) found itself taking a more strict perspective against commercial alliances than the unpaid community editors.